PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN MANUFAKTUR YANG TERMASUK DALAM DAFTAR EFEK SYARIAH - IGNES JANUAR CAHYADI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to analyze the influence of firm size, profitability, firm growth, assets structure, tax paid, safety consideration, and business risk toward capital structure and to analyze the influence of business risk toward capital structure with managerial ownership as moderating variable, among manufacturing companies included in the List of Islamic Securities.The samples in this research are all of the manufacturing companies included in the List of Islamic Securities, in the period 2010 until 2012. Only 50 companies meet the criteria and taken as samples. The samples of this research collected using purposive sampling and this research used multiple regression analysis to test the hypothesis. The conclusion of this research shows that firm size, firm growth, assets structure, safety consideration influence capital structure in the positive sign while profitability and business risk influence capital structure in the negative sign. On the other hand, tax paid do not influence capital structure. This research also show that managerial ownership has proven as moderating variable that strengthens the negative effect of business risk toward capital structure.